Differential expression of hMLH1 and hMSH2 is related to bladder cancer grade, stage and prognosis but not microsatellite instability. - Catto, J; Xinarianos, G; Burton, J; Meuth, M; Hamdy, F (2003)
Defects in the DNA mismatch repair proteins result in microsatellite instability and malignancy in hereditary non-polyposis colorectal carcinoma (HNPCC). However, the role of mismatch repair (MMR) proteins and microsatellite instability (MSI) in transitional cell carcinoma of the bladder is less clear. In our study, the expression of 2 MMR proteins and the frequency of MSI in Transitional cell carcinoma of the bladder (TCC) were investigated. One hundred eleven patients with TCC of the bladder were studied, with complete clinicopathological data (median follow up of 5 years, range 5-16 years). Immunohistochemistry was used to detect the expression levels of hMLH1 and hMSH2. Microsatellite analysis for 14 loci (10 loci from the Bethesda consensus panel and the repeats in the TGFbetaR2, BAX, hMSH3 and hMSH6 genes) was performed on 84 tumors. Reduced expression of either MMR protein was seen in 26 of 111 tumors (23%). Reduced expression was seen more commonly in muscle invasive (p<0.03) and high grade TCC (p<0.03) than in superficial, low grade tumors. By 5 years, reduced expression of either MMR protein was associated with fewer recurrences of superficial tumors (p=0.015) and fewer relapses in all tumors (p=0.03), compared to tumors with normal expression. Nine tumors had reduced expression of both MMR proteins, analysis which suggests a synergistic reduction in expression (p=0.001). MMR expression was related to patient age, younger patients being more likely to have reduced MMR expression than older patients (p<0.01). MSI was seen at multiple loci in 1 tumor (1%) and at a single locus in 6 tumors (7%). MSI was not associated with MMR expression. Our findings indicate that reduced expression of the MMR proteins may have an important contribution in the development of a subset of TCCs and suggest a potential role for MMR expression as prognostic indicators.